Tahuri: Symbol of the Christian-Muslim Community Peace in Tehoru and Telutih, Central Maluku, Indonesia - Resa Dandirwalu; Handry Yance Rehy (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
This study departs from the social conflict in Maluku in 1999. The conflict separated the Christian and Muslim communities in Tehoru and Telutih Districts, Central Maluku, Indonesia. Then, the Regional Government of Central Maluku Regency reconciled by returning the Christian community to both Districts. However, the Christian community still felt anxious and insecure because peace is only carried out by the Government Agency. Both communities created Tahuri symbol as a peace symbol between them.  In 2014, they made Tahuri monument, and it was inaugurated on December 7, 2016. Therefore, the purpose of this study was to find the meaning of Tahuri symbol as peace of Christian and Muslim communities in  Tehoru and Telutih Districts. The focus of this study the peace symbol created by both communities of Tehoru and Telutih. This study employs Symbolic Anthropology to find the meaning of symbols accepted by humans through relations with others and their natural world. Data gathered through observation and interviews in both districts and presented using a descriptive analysis model. The result shows that Tahuri symbol has two important principles: the inclusive principle and mutual trust principle. Besides, for the Christian and Muslim communities, the Tahuri symbol means collective identity and social cohesion. Both communities contextualized these two principles and meanings in their social and religious life so that social and religious dynamics cannot reduce them. They live in harmony. The peace through the Tahuri symbol is maintained to this day.